2010
DOI: 10.1097/gim.0b013e3181cd6689
|View full text |Cite
|
Sign up to set email alerts
|

The role of race and trust in tissue/blood donation for genetic research

Abstract: Background Public willingness to donate tissue samples is critical to genetic research. Prior work has linked minority status and mistrust with less willingness to provide specimens. Some have suggested recruitment of prior research participants to address these barriers. We present data from a genetic epidemiology study with a request for blood and/or saliva specimens to: 1) measure willingness to donate tissue/blood samples, 2) identify demographic, trust, and other factors associated with willingness to don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 22 publications
8
84
1
Order By: Relevance
“…Likewise, our team, especially our NWP team, in combination with many other studies (Bates et al 2005;Bussey-Jones et al 2010;Corbie-Smith 1999;Furr 2002;Tambor et al 2002), continue to re-state the need for investigators' awareness regarding the challenge of overcoming the hesitation or refusal to participate in research and mistrust by African Americans and other minority groups. Reluctance to respond therefore makes the process of African American recruitment inherently different from the recruitment of White/European Americans.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, our team, especially our NWP team, in combination with many other studies (Bates et al 2005;Bussey-Jones et al 2010;Corbie-Smith 1999;Furr 2002;Tambor et al 2002), continue to re-state the need for investigators' awareness regarding the challenge of overcoming the hesitation or refusal to participate in research and mistrust by African Americans and other minority groups. Reluctance to respond therefore makes the process of African American recruitment inherently different from the recruitment of White/European Americans.…”
Section: Discussionmentioning
confidence: 93%
“…The hesitation or refusal is based on a myriad of reasons not limited to the tragic history of the Tuskegee experiments (Corbie-Smith 1999) and impact of other research such as the more recent Henrietta Lacks example (Skloot 2010). Minority research participation in the USA is indirectly or directly impacted by the sociopolitical legacy of slavery, Jim Crow policies, and lingering perceptions and reality of racism and discrimination (Bussey-Jones et al 2010;Johnson et al 2011;Satia et al 2005). Part of the solution rests on the abilities of investigators and participants from diverse racial/ethnic backgrounds to understand and perceive the world through each other's worldviews and adapt recruitment strategies to reflect knowledge learned.…”
Section: Discussionmentioning
confidence: 99%
“…Their specific mistrust of human genetics research is only more recently becoming apparent (Bonham et al 2009;Bussey-Jones et al 2010;McDonald et al 2012;Skinner et al 2008). What researchers have found is that African Americans tend to view genetic screening as eugenic in motivation and harmful to society (Beeson and Duster 2002), and compared to European Americans, they are less optimistic about genetic testing (Achter et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a 2007 study assessing the reasons why acute care patients with cardiovascular disease chose non-participation in Biobanks, results indicated that both age and certain minority demographic characteristics were associated with less likelihood of participation; with the main reason being wanting to avoid a blood draw [3] . Developers must also acknowledge the lack of trust by ethnic minority groups toward medical institutions [19,32] . Over the years, as more Biobanks have been created, the idea of community consultation has become a necessity as community consultation incorporates the ideas, concerns and needs of the patients into the development of Biobanks.…”
Section: Discussionmentioning
confidence: 99%